EXTREMELY PREMATURE NEONATES EXHIBIT INSULIN RESISTANCE. Issue 1 (14th December 2015) - Salis, Emma R; Reith, David M; Broadbent, Roland S; Wheeler, Benjamin J; Medlicott, Natalie J
Abstract : Introduction: Preterm birth disrupts normal timing of physiological adaptation of insulin secretion putting premature neonates at risk of abnormal glucose homeostasis. The insulin/C-peptide (I/CP) ratio gives an indication of insulin clearance but has not been reported in neonates. Premature neonates have significantly higher fasting levels of GLP-1 than adults that increase even further with feeding. Aims: To determine I/CP and insulin/blood glucose level (I/BGL) ratios in neonates and the effect of postmenstrual age (PMA) on these measures. To determine GLP-1 concentrations in never-fed versus fed neonates. Methods: Plasma samples were obtained from 102 neonates admitted to Dunedin Hospital NICU. Plasma was analysed for insulin and C-peptide using chemiluminescent kits (Invitron, UK), GLP-1 and glucagon using ELISA (BioCore Pty Ltd, Australia). Statistical analyses were performed using Stata/IC (v11.2). Results: The PMA range was 24–51.3 weeks. The median I/CP ratio was 0.44, 95% CI (0.44, 0.61). The median I/BGL ratio was 9.3, 95% CI (8.2, 10.6). Linear regressions of ln-transformed data were performed. I/CP and I/BGL ratios were significantly affected by PMA (p<0.01). Negative correlations were found (r=−0.21 and −0.35 for I/CP and I/BGL respectively, p<0.01) and I/CP changed around 34 weeks. Insulin concentrations were negatively correlated (r=−0.38, p<0.01) with increasing PMA. ANOVA showed higher GLP-1 concentrations (p=0.011) in fed versus never-fed neonates. Conclusions: These findings indicate insulin resistance in premature neonates prior to 34 weeks gestation. The significantly higher GLP-1 concentrations in fed neonates confirm that GLP-1 increases with the establishment of feeding.